Projection of Residential Energy Consumption in Peru (2005-2030) - Rojas Lazo, Oswaldo (2009)
This paper presents a methodology for determining the projection of national energy consumption in the household sector for the period 2005 - 2030 (Model for Energy Demand Analysis MAED_D). The paper starts with the development of national energy sector (supply and demand of primary and secondary), continuing with the analysis of the main indicators of the energy crisis of the explanatory variables and energy consumption in the household sector. After this analysis is done using the software entered demographic factors and consumer habits of the household sector. The results show that energy consumption based on the year 2005 (4.536 GWa) could increase to 7845 GWa in 2030.